COPOLYMERIZATION STUDY OF(N-ACRYLOY AMIDE) MONOMER WITH BUTY ACRYLATE AND DETERMINATION OF THE REACTIVITY RATIO - Tarik A. Mondyl (مجلة جامعة الانبار للعلوم الصرفة, 2012)
In the present study the copolymerizatioin was carried out between Isobutyl acrylat (IBA) and butyl acrylate with different molar ratio. ( 0.2 m1/0.8 m2 ----- to 0.8 m1/0.2 m2 ) Where m1 represent (IBA) and m2 (BA) . The Polymarization was carried out by free radical using (AIBN) as inititor at 70ºC. The reactivity ratios r1 and r2 of monomers participated in the reaction which leads to (IBA-co-BA) system . where Calculated using three method mayo- lewis as well as Finemane – Ross and Kelen-Tudos were used method to measure the percentage of reactivity ratios were adopted .The percentage of measure reactivity was found to be r1= 0.084 and r2 = 2.022 This means that the reactivity of butyle acrylat (BA) m2 is greater than reactivity of (IBA) m1 and the copolymer is Random because the multiplication product of r1 with r2 equal to 00169 which is less than one. r1 r2 than one.